Carbon monoxide concentrations in paediatric sepsis syndrome. Issue 10 (19th September 2003) - Shi, Y; Pan, F; Li, H; Pan, J; Qin, S; Jiang, D; Shen, C
Abstract : Plasma carbon monoxide (CO) concentrations were measured in 12 patients with sepsis syndrome. CO concentrations were found to be significantly increased in patients compared with those in 30 normal controls. Patients with septic shock had significantly higher plasma CO concentrations than those without shock. Results suggest that CO might play an important role in paediatric sepsis syndrome.